2020
DOI: 10.1002/aqc.3451
|View full text |Cite
|
Sign up to set email alerts
|

Swimming nets have positive effects on populations of the endangered White's seahorse Hippocampus whitei

Abstract: Habitat degradation and destruction arising from rapidly increasing urbanization represents one of the most significant threats to biodiversity. Human populations are continuing to increase around coastal regions, and as marine habitats are displaced by artificial structures it is important to understand how marine species may be impacted by these changes in habitat availability. The endangered seahorse Hippocampus whitei has been observed inhabiting protective swimming nets in Sydney Harbour, Sydney, Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A broad habitat spectrum, as seen in H. reidi [120][121][122], probably enhances a species' suitability as an aquarium pet. As seahorses are poor swimmers, the availability of a holdfast is an important habitat factor [123,124], which may explain why some species have no problem in using artificial substrates to cling on [125][126][127][128][129][130][131][132]. Large seahorse species that are commonly fished, such as H. reidi (Figure 3b), are overall less specific in their habitat requirements but share several traits with small congenerics, such as the use of camouflage and an immobile body posture while using the tail as holdfast [29,108] (Figure 3b), but some species are able to change coloration as part of their courtship behavior [109,110] or need for camouflage [103].…”
Section: Body Size and Habitat Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad habitat spectrum, as seen in H. reidi [120][121][122], probably enhances a species' suitability as an aquarium pet. As seahorses are poor swimmers, the availability of a holdfast is an important habitat factor [123,124], which may explain why some species have no problem in using artificial substrates to cling on [125][126][127][128][129][130][131][132]. Large seahorse species that are commonly fished, such as H. reidi (Figure 3b), are overall less specific in their habitat requirements but share several traits with small congenerics, such as the use of camouflage and an immobile body posture while using the tail as holdfast [29,108] (Figure 3b), but some species are able to change coloration as part of their courtship behavior [109,110] or need for camouflage [103].…”
Section: Body Size and Habitat Requirementsmentioning
confidence: 99%
“…A broad habitat spectrum, as seen in H. reidi [120][121][122], probably enhances a species' suitability as an aquarium pet. As seahorses are poor swimmers, the availability of a holdfast is an important habitat factor [123,124], which may explain why some species have no problem in using artificial substrates to cling on [125][126][127][128][129][130][131][132].…”
Section: Body Size and Habitat Requirementsmentioning
confidence: 99%
“…Whilst habitats have declined across its range, H. whitei has shown an ability to adapt by utilising artificial habitats such as protective swimming nets (Hellyer et al, 2011;Simpson et al, 2021a;Simpson et al, 2021b) and purposefully designed artificial habitats known as seahorse hotels (Simpson et al, 2020). It was recently shown that adult H. whitei select artificial habitats over natural habitats (Simpson et al, 2019), similar to that of the only other Endangered seahorse species, Hippocampus capensis in South Africa (Claassens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Caulerpa prolifera ) are rarely used (Olivotto et al., 2008), likely due to difficulties in their long‐term maintenance. While inter‐specific differences may exist regarding holdfast preferences and seahorse size, only a few studies have focussed on this topic in the wild or in rearing facilities (Claassens et al., 2018; Correia et al., 2013, 2015; Faleiro et al., 2008; Simpson et al., 2019, 2020a, b). Understanding seahorse preferences will help to improve seahorse fitness at high stocking densities and to increase fish production by providing better conditions for growth.…”
Section: Introductionmentioning
confidence: 99%